Compreender a (in)disciplina na sala de aula: uma análise das relações de controlo e de poder - Maria Preciosa Silva; Isabel Pestana Neves (Universidade do Minho, 2006)
The study is part of a broader research which intended at understanding the relation between students disruptive behaviours and teachers pedagogic practices and finding out reasons underlying that relation. Theoretically it is based on Bernsteins theory of pedagogic discourse. The study is centred on four students, from two science classes of the 6th year of schooling (ages 11- 12), who had showed distinct behaviours. It adresses the following objectives: (1) analyse students behaviours in terms of the interaction between their socio-affective dispositions and their specific coding orientation for power and control relations that characterise the regulative context of teachers pedagogic practices; (2) analyse the extent to which specificities of the interaction may explain different levels of disruptive behaviours. The study suggests that disruptive behaviours in the classroom are the result of the interaction between students socio-affective dispositions to teachers pedagogic practices and their specific coding orientation to control relations that characterise the regulative context of those practices. It also suggests that distinct specific coding orientations to power relations between teacher and students may explain distinct levels of disruptive behaviours.